Exploring patients' experience and perception of being diagnosed with bladder cancer: a mixed‐methods approach. (12th February 2020) - Tan, Wei Shen; Teo, Chin Hai; Chan, Delcos; Ang, Kar Mun; Heinrich, Malgorzata; Feber, Andrew; Sarpong, Rachael; Williams, Norman; Brew‐Graves, Chris; Ng, Chirk Jenn; Kelly, John; ,
Abstract : Objective: To determine patient experience and perception following a diagnosis of non‐muscle‐invasive bladder cancer (NMIBC). Patient and methods: Patients were part of a prospective multicentre observational study recruiting patients with NMIBC for a urine biomarker study (DETECT II; ClinicalTrials.gov: NCT02781428). A mixed‐methods approach comprising: (i) the Brief Illness Perception Questionnaire (Brief‐IPQ) and (ii) semi‐structured interviews to explore patients' experience of having haematuria, and initial and subsequent experience with a NMIBC diagnosis. Both assessments were completed at 6 months after NMIBC diagnosis. Results: A total of 213 patients completed the Brief‐IPQ. Patients felt that they had minimal symptoms (median [interquartile range, IQR] score 2 [0–5]) and were not particularly affected emotionally (median [IQR] score 3 [1–6]) with a minimal effect to their daily life (median [IQR] score 2 [0–5]). However, they remained concerned about their cancer diagnosis (median [IQR] score 5 [3–8]) and felt that they had no personal control over the cancer (median [IQR] score 2 [2–5]) and believed that their illness would affect them for some time (median [IQR] score 6 [3–10]). A significant association with a lower personal control of the disease ( P  < 0.05) and a poorer understanding of the management of NMIBC ( P  < 0.05) was seen in patients aged >70 years. Many patients were uncertain about the cause of bladder cancer. Qualitative analysis found that at initial presentation of haematuria, most patients were not aware of the risk of bladder cancer. Patients were most anxious and psychologically affected between the interval of cystoscopy diagnosis and transurethral resection of bladder tumour (TURBT). Following TURBT, most patients were positive about their cancer prognosis. Conclusion: Patients with NMIBC have a poor perception of disease control and believe that their disease will continue over a prolonged period of time. This is particularly more pertinent in the elderly. Patients are most psychologically affected during the interval between cancer diagnosis following cystoscopy and TURBT. Health awareness about bladder cancer remained poor with a significant number of patients unaware of the causes of bladder cancer. Psychological support and prompt TURBT following bladder cancer diagnosis would help improve the mental health of patients with NMIBC.